Profiles and residents' perception of environmental sound and music activities in Bandar Dataran Segar, Port Dickson, Malaysia - Toh, Phyllis Chze Woon (2014)
Bandar Dataran Segar is one of the newly developed townships located at the non-beach site in Port Dickson, in the state of Negeri Sembilan. It comprises hundreds of units of mixed commercial buildings, shops and houses (link houses, semi-detached, bungalow). This signifies the many new communities developing in the suburb of present Malaysia. Concerned about the development of future generations in dealing with the environmental sound and music activities, this study takes Bandar Dataran Segar as an example for its typical setting for a new township within the socio-economic context of Port Dickson. The objectives of the research are to determine and analyse each sound profiles, to identify the music in sound profiles of the temporary events such as celebrations and festivals, and, to evaluate the perception of residents regarding the sound environment in Bandar Dataran Segar. Approximately 200 clips of sound in and surround Bandar Dataran Segar have been recorded. These clips have been screened through and grouped based on researcher designed ‘Typology of Sound Profiles’. Selected sound profiles have been analysed according to the subareas of different building types and costs at different times, and according to the temporary events such as celebrations and festivals. In order to obtain the awareness and perception of the residents regarding the sound environment in Bandar Dataran Segar, 40 residents participated in filling in structured questionnaires and interviews where they provided views about sound environment of the immediate areas they stay and the entire township in general. To probe further into their awareness,listening tests were also conducted to determine their ability in recognizing various sound sources existing in the township. The findings of the study reveal that the types and cost of houses do not necessarily correspond with the quality of sound environment. The high cost housing area’s sound profiles are complicated by the external sounds created by infrastructure or commercial activities nearby. In reverse, the medium low cost housing area is the least disturbed by constant anthrophony such as sound of machineries, air-conditioner compressors, and commercially run swallow houses. Hence, it is the most serene among all areas in this township. Music activities in sound profiles of temporary events such as celebrations and festivals display the characteristics of ‘active-featured’ as its main characteristic,where it consists of intersection of controlled-anthrophony, with constant presence of physiological-anthrophony. Residents’ observation of the sound environment of this township include the identification of the time zone that are the noisiest and quietest within their respective residential area, and areas within the entire township that has pleasant as well as unwanted sound environment. The two ends of the typology spectrum namely ‘passive-incidental’ and ‘active-featured’ seem to be the least recognizable sound types by the residents. Studies on sound waste, musical choice and musical production are recommended to further understand the sound environment in Bandar Dataran Segar as well as in other similar development areas.